2005
DOI: 10.2223/jped.1422
|View full text |Cite
|
Sign up to set email alerts
|

The impact of training based on the Baby-Friendly Hospital Initiative on breastfeeding practices in the Northeast of Brazil

Abstract: Objective: To evaluate the impact of training based on the Baby Friendly Hospital Initiative on breastfeeding practices in maternity wards and during the first 6 months of life.Methods: Ninety percent of nursing auxiliaries and midwives were trained at two institutions (A and B) in Palmares, Pernambuco state. Three hundred and thirty-four mothers were interviewed within the first 48 hours and 10 days after childbirth to evaluate breastfeeding practices at the maternities and fulfillment of steps four through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
(28 reference statements)
1
23
0
2
Order By: Relevance
“…All the practices assessed are, to some extent, included in the BFHI Ten Steps. Thus, this study corroborates previous investigations that have shown a positive impact of the BFHI on breastfeeding indicators (Braun et al, ; Coutinho, Lima Mde, Ashworth, & Lira, ; de Oliveira, Camacho, & Tedstone, ; Lamounier et al, ; Passanha, Benicio, Venancio, & Reis, ; Perez‐Escamilla, Martinez, & Segura‐Perez, ; Venancio, Saldiva, Escuder, & Giugliani, ). This impact has already been demonstrated also in the city where the present study was carried out (Braun et al, ) and in Brazil as a whole (Venancio, Saldiva, Escuder, & Giugliani, ).…”
Section: Discussionsupporting
confidence: 92%
“…All the practices assessed are, to some extent, included in the BFHI Ten Steps. Thus, this study corroborates previous investigations that have shown a positive impact of the BFHI on breastfeeding indicators (Braun et al, ; Coutinho, Lima Mde, Ashworth, & Lira, ; de Oliveira, Camacho, & Tedstone, ; Lamounier et al, ; Passanha, Benicio, Venancio, & Reis, ; Perez‐Escamilla, Martinez, & Segura‐Perez, ; Venancio, Saldiva, Escuder, & Giugliani, ). This impact has already been demonstrated also in the city where the present study was carried out (Braun et al, ) and in Brazil as a whole (Venancio, Saldiva, Escuder, & Giugliani, ).…”
Section: Discussionsupporting
confidence: 92%
“…Additional quasi‐experimental and observational studies also provide indirect evidence in support of this finding (i.e. low ABF rates in the short term in the absence of a well‐implemented step 10) (de Oliveira et al, ; Silva et al, ; Coutinho et al, ; Lutter et al, ). The central importance of step 10 calls for increasing investments on structured programmes at the community level such as the Baby Friendly Primary Health Care initiative from Brazil (de Oliveira et al, ) and the Supplemental Nutrition Program for Women, Infants and Children (WIC) breastfeeding peer counselling programme in the United States [National Academies of Sciences, Engineering, and Medicine ()].…”
Section: Resultsmentioning
confidence: 87%
“…Fourteen pre-post studies without a parallel comparison group were conducted in Brazil, Chile, Croatia, India, Italy, Spain, Turkey, UK and the United States. Five studies were of very low quality (Dasgupta et al, 1997;Bosnjak et al, 2004;Coutinho et al, 2005b;Caldeira & Goncalves, 2007;Duyan Camurdan et al, 2007), eight of low quality (Wright et al, 1996;Cattaneo & Buzzetti, 2001;Philipp et al, 2001;Braun et al, 2003;Philipp et al, 2003;Garcia-de-Leon-Gonzalez et al, 2011;Ingram et al, 2011;Zakarija-Grkovic et al, 2012) and one of moderate quality (Valdes et al, 1993). Studies' description and findings.…”
Section: Pre-post Bfhi Implementation Without Parallel Comparison Groupmentioning
confidence: 99%
“…Breastfeeding categories were analyzed together due to the low frequency of exclusive breastfeeding in the studied region. 37 It is probably for this reason that there was no association between rapid postnatal weight gain and the duration of breastfeeding. However, breastfeeding proved to be a protective factor in relation to the body measurements at 8 years old, as children who were breastfed for longer had lower mean values of BMI and WC.…”
Section: Discussionmentioning
confidence: 99%